2011
DOI: 10.1007/s00248-011-9910-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotactic Bacteria in Microcosms Originating from the French Mediterranean Coast Subjected to Oil Industry Activities

Abstract: Magnetotactic bacteria (MTB) mineralize nanosized magnetite or greigite crystals within cells and thus play an important role in the biogeochemical process. Despite decades of research, knowledge of MTB distribution and ecology, notably in areas subjected to oil industry activities, is still limited. In the present study, we investigated the presence of MTB in the Gulf of Fos, French Mediterranean coast, which is subjected to intensive oil industry activities. Microcosms containing sediments/water (1:2, v/v) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 44 publications
3
34
0
Order By: Relevance
“…Other workers found that salinity, nitrate concentrations, and sulfate concentrations correlate with the amounts of MTB (16,19,26,33). We observed worms and small aquatic plants living in the sediment.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Other workers found that salinity, nitrate concentrations, and sulfate concentrations correlate with the amounts of MTB (16,19,26,33). We observed worms and small aquatic plants living in the sediment.…”
Section: Discussionmentioning
confidence: 47%
“…2). Initially, MTB rods and MTB spirilla predominated, but MTB cocci became the dominant group after day 37, which has been found in natural habitats (16,19,26,27). Moreover, when MTB cocci had similar spatial distributions between adjacent days of counting, MTB spirilla were concentrated in different places between those same adjacent days of counting and vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, within the OAI itself, different species of MTB occupy different positions that represent different specific chemical conditions at that depth. Biogeographic studies indicate that some environmental parameters such as salinity, temperature, nitrate, or sulfur compounds could explain MTB abundance or community differences (17)(18)(19)(20)(21). One study reported that despite the fact that the largest proportion of MTB appears to be detected within the suboxic zone, a strict correlation between the distribution of MTB and individual geochemical parameters has never been shown (22).…”
Section: Ecology and Biogeographic Distribution Of Magnetotactic Bactmentioning
confidence: 99%
“…Although this may not seem significant, there are relative few groups or investigators studying the diversity of MTB, although this number is now increasing. As stated above, the diversity of MTB has been studied mainly in several locations in North America (2, 26-28, 31, 32, 44, 53, 75, 171), Brazil (19, 42, 86, 148, 166), China (17-21, 31-33), Germany (22, 34, 45, 93, 94, 96, 145, 150), and France (21,49,89). Clearly, then, little is known regarding MTB of the Southern Hemisphere.…”
Section: Is the Known Diversity Of Magnetotactic Bacteria An Underestmentioning
confidence: 99%